POSSIBLE CONSEQUENCES OF THE REFUSAL TO SWITCH TO A DIGITAL CURRENCY IN AZERBAIJAN (Scientific journal of the Fergana State University, 2024)
It is known that the world wants to achieve fast and high achievements in electronicization, digitization, modern scientific and technical progress in order to maintain its existence in the rapid flow of the Fourth Industrial Revolution. In Azerbaijan, the creation of a digital national currency and the transition to the use of that currency are delayed for some reasons. I wonder what the real reason for the delay is?Today's successes of our country were founded by the election of the victorious leader and historical figure Mr. Ilham Aliyev as the President of the Republic of Azerbaijan 20 years ago. In the past 20 years, 4 consecutive state programs related to the socio-economic development of the regions have been adopted and implemented. In addition to the 44-day war, Mr. President fought single-handedly against countries with great influence in world political leadership, created new geostrategic realities, gave importance to the existence of international law, and freed our lands and souls from occupation as the Victorious Commander of the victorious nation. With this, he engraved his name in history with golden letters and left a prosperous state and statehood to the people and heritage of Azerbaijan for the future.